, Brežnevinio sąstingio" praeities deformacijos lietuviškuose kino ir televizijos vaidybiniuose filmuose ( 1968-1980 metai) - Kaminskaitė-Jančorienė, Lina (Lietuvos istorijos studijos, 2008)
The objective of this work is to identify collective memory shapes in Lithuanian fiction TV and cinema film during the Brezhnevian period (1968-1980). According to new popular theoretical approaches, this work analyses the specific source of history—fiction film—so this research brings Lithuanian fiction film up-to-date with usual resources of history. According to the research conclusions, new methodological approaches are made, which can help to classify fiction films in which past representations can be seen. On the other hand, the analysis of archival origins helps to reconstruct the Soviet film industry system of Lithuania (censorship, the specific "control-gear" of films) and contextual analysis, which identifies the main political and creative displacements. Film content research helps to identify the reconstructions of the past and its sociohistorical approaches.